2003
DOI: 10.1038/nature02207
|View full text |Cite
|
Sign up to set email alerts
|

A conspicuous nickel protein in microbial mats that oxidize methane anaerobically

Abstract: Anaerobic oxidation of methane (AOM) in marine sediments is an important microbial process in the global carbon cycle and in control of greenhouse gas emission. The responsible organisms supposedly reverse the reactions of methanogenesis, but cultures providing biochemical proof of this have not been isolated. Here we searched for AOM-associated cell components in microbial mats from anoxic methane seeps in the Black Sea. These mats catalyse AOM rather than carry out methanogenesis. We extracted a prominent ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
308
0
3

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 338 publications
(317 citation statements)
references
References 29 publications
6
308
0
3
Order By: Relevance
“…This enzyme catalyzes the final reaction in biogenic methane production and its amino acid sequence is highly conserved among all methanogenic archaea (Ellermann et al, 1988;Grabarse et al, 2000). In AOM it is presumed to function in reverse (Hallam et al, 2003;Krü ger et al, 2003;Wang et al, 2013). Transcripts for all subunits were significantly more abundant in the LI (Supplementary Figure S2), and were absent in the oxic control sample.…”
Section: Methanogenesis and Aommentioning
confidence: 95%
“…This enzyme catalyzes the final reaction in biogenic methane production and its amino acid sequence is highly conserved among all methanogenic archaea (Ellermann et al, 1988;Grabarse et al, 2000). In AOM it is presumed to function in reverse (Hallam et al, 2003;Krü ger et al, 2003;Wang et al, 2013). Transcripts for all subunits were significantly more abundant in the LI (Supplementary Figure S2), and were absent in the oxic control sample.…”
Section: Methanogenesis and Aommentioning
confidence: 95%
“…The retrieved mcrAderived sequences form a separate cluster with at least 6% amino-acid divergence to other sequences within the mcrA groups a-b (Figure 4c). In comparison to mcrA from methanogenic archaea, the present sequence contains a modification (motif VX 2 CCX 4 CX 5 C), which has been previously observed in the abundant nickel protein of ANME-1 consortia in a cold habitat (Krü ger et al, 2003). The most frequently retrieved bacterial 16S rRNA clone sequences represent a lineage distantly related to Desulfurella spp., sulfur-reducing thermophilic Deltaproteobacteria ( Figure 4b; Table 1).…”
Section: Thermophilic Anaerobic Methanotrophy T Holler Et Almentioning
confidence: 99%
“…These horizons are usually populated by archaea (ANME groups) and bacteria of distinct phylogenetic lineages clustering with methanogens and Deltaproteobacteria, respectively (Boetius et al, 2000;Knittel and Boetius, 2009). The ANME archaea are thought to oxidize the methane in principle via a reversal of the reactions of methanogenesis (Zehnder and Brock, 1979;Krü ger et al, 2003;Hallam et al, 2004;Scheller et al, 2010). Biochemical studies so far focused on the ANMEassociated protein that is closely related to methylcoenzyme M reductase (Mcr), the nickel enzyme catalyzing the terminal step in methanogenesis (Thauer, 1998;Hallam et al, 2003;Krü ger et al, 2003;Scheller et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…AOM is a form of reversed methanogenesis: AOM is like methanogenesis inhibited by bromoethanesulfonate (BES; Nauhaus et al 2005), ANME-1 cells were found to contain most of the genes typically associated with CH 4 production (Hallam et al 2003(Hallam et al , 2004 and an analogue of the methyl-coenzyme M reductase was found to make up 7% of the extracted soluble proteins from an AOM mediating microbial mat from the Black Sea (Krüger et al 2003). The DG°0 of the reduction of methyl-coenzyme M to produce CH 4 is -30 (±10) kJ mol -1 , the back reaction becomes exogenic when the product to substrate concentration ratio is *10 5 , such a ratio is physiologically not unrealistic (Thauer and Shima 2008).…”
Section: Reversed Methanogenesismentioning
confidence: 99%